THE CLUSTER FORM OF ORGANIZATION AND THE PROSPECTS FOR ITS APPLICATION TO PROVIDE THE SUSTAINABLE DEVELOPMENT OF COOPERATIVE ENTREPRENEURSHIP - I. Tinyakova, Viktoriya; I. Morozova, Natalia; V. Konovalova , Oksana; Yu. Proskurina, Irina; B. Falkovich, Elena (Gênero & Direito, 2020)
As a promising model for the development of the system of consumer cooperation, territorial-production clusters that have been tested by world practice can play the role of overcoming the antagonism of interests between agricultural producers and processing enterprises. The association of producers leads to a chance for a more complete utilization of capacities and thereby less costs, which reduces the percentage of production risk, and the processing enterprises provide themselves with a reliable raw material base and a guarantee for the sales of finished products. The cluster allows one to balance the cooperation and rivalry (competition) of the cluster’s members, since “the cluster is jointly and severally liable to its customers”. It is this principle that allows us to take this organizational form as the most promising one in terms of efficiency. Since it is not only the manufacturer of the final product who is responsible to the “buyer” in economic form, but all the institutional units of the cluster share entrepreneurial risks among themselves and receive a prize for these risks - profit. As criteria for the feasibility of forming a cluster, it is necessary to consider not only the economic effects achieved by combining the economic efforts of interested business subjects into a single production-distribution chain within which added value is created, but also the institutional structures of the non-economic sphere - educational, innovative, administrative and others. This form of integration becomes possible due to the flexibility of the cluster structure and the matrix-network principle of its functioning, which creates additional opportunities for the cluster to survive in conditions of fierce international competition.